2019
DOI: 10.1111/fog.12451
|View full text |Cite
|
Sign up to set email alerts
|

Bonga shad (Ethmalosa fimbriata) spawning tactics in an upwelling environment

Abstract: Successful recruitment in small pelagic fish populations inhabiting upwelling zones is subject to variation in fecundity and is driven by spatial and temporal fluctuations in environmental conditions, that is, mainly sea surface temperature, salinity and food availability. These fluctuations in abiotic factors have stimulated small pelagic fish populations to exhibit specifically adapted spawning tactics. To better understand to what extent a short‐lived exploited fish species such as bonga shad Ethmalosa fimb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…According to Hattab et al [87] and Basilone et al [88,89], environmental changes may have impacts on the size and fecundity of small pelagic species. These results were also confirmed by Baldé et al [4,6] in West Africa. Indeed, growth is strongly influenced by environmental variations which lead to a decrease or increase in fecundity of small pelagics in Senegal.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…According to Hattab et al [87] and Basilone et al [88,89], environmental changes may have impacts on the size and fecundity of small pelagic species. These results were also confirmed by Baldé et al [4,6] in West Africa. Indeed, growth is strongly influenced by environmental variations which lead to a decrease or increase in fecundity of small pelagics in Senegal.…”
Section: Discussionsupporting
confidence: 84%
“…The biological parameters of small pelagic fishes are expected to differ with habitat, environment factors, and overfishing [3,4,6]. The current study showed that the asymptotic length (L ∞ ) of S. pilchardus was 30.5 cm maximum at six years, and that this value differed significantly to other countries in northwest Africa (Table 2).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Previous studies have demonstrated the importance of oceanographic structures to these spawning activities, as well as the direct effects of temperature, salinity and other abiotic factors (Bakun, 2006; Brunel et al., 2017; Kloppmann et al., 2001; Lough et al., 1996). For example, most of the intense spawning areas of SPF appear within regions of high zooplankton productivity, which are associated with the main upwelling areas or meso‐scale hydrodynamic structures such as eddies and ocean fronts (Aceves‐Medina et al., 2009; Baldé et al., 2019; Peck et al., 2013; Somarakis & Nikolioudakis, 2007). However, some SPF use different spawning strategies to avoid the strong passive transport of their eggs and larvae or the strong turbulence and instability of the water column in some intense upwelling systems (Dias et al., 2014; Lluch‐Belda et al., 1991; Parrish et al., 1981; Tiedemann et al., 2017), suggesting that SPF show adaptive phenotypic characteristics in different oceanographic systems.…”
Section: Introductionmentioning
confidence: 99%